2006
DOI: 10.1080/17461390600676200
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant analysis of game‐related statistics between basketball guards, forwards and centres in three professional leagues

Abstract: The aim of the present paper was to examine the differences in game-related statistics between basketball guards, forwards and centres playing in three professional leagues: National Basketball Association (NBA, superior level) in the USA, Associacio ´n de Clubs de Baloncesto (ACB, one of the best European leagues) in Spain and Liga de Clubes de Basquetebol (LCB, inferior level) in Portugal. We reasoned that the knowledge of these differences could allow the coaches to better establish and monitor playing patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
169
1
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(192 citation statements)
references
References 4 publications
11
169
1
11
Order By: Relevance
“…Similar to the current results, assists and steals were also reported be related to game success in disparate games. 5 These results reinforce the importance and dominance of the teams' tactical organization for game success. Another variable that distinguished winning teams from losing teams was free-throw shot accuracy.…”
Section: Determinant Variables For the Games Victories In Function Osupporting
confidence: 59%
See 1 more Smart Citation
“…Similar to the current results, assists and steals were also reported be related to game success in disparate games. 5 These results reinforce the importance and dominance of the teams' tactical organization for game success. Another variable that distinguished winning teams from losing teams was free-throw shot accuracy.…”
Section: Determinant Variables For the Games Victories In Function Osupporting
confidence: 59%
“…4 With increasing competition level, each successful skill and tactical action performed during the game becomes an important contributor to team success. The statistical analysis of such skills and actions has been previously performed during games within the Spanish League 5 with many skills/actions identified as significant factors for team success. For example, winning teams were distinguished from losing teams based upon 1-point (freethrow), 2-point and 3-point shooting accuracy, the number of missed shots secured by the defensive players (defensive rebounds), the total number of times a player assists a teammate scoring (assists), the number of times a ball is stolen from an opposing player (steals) and the number of rule infractions involving physical contact (fouls) completed by players.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have reported that assists were a discriminating game-related statistic between senior and junior basketball players' performances, suggesting that this is also a measure of player and team experience and maturity (Sampaio, Ibanez, & Feu 2004). These actions are mostly performed by guards (Sampaio, Janeira, Ibanez, & Lorenzo, 2006;Taxildaris et al, 2001). Therefore, it is suggested that the best teams have players in this specific position better prepared to execute these tasks, building in practices and promoting in competition a stronger within-team offensive communication (Heuze, Rainbault, & Fontayne, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been suggested that less effective teams use ball dribbling more frequently (Gomez et al, 2006), which can increase the probability of a steal. On the other hand, blocks occur mostly inside the court restrictive area and are usually performed by centres (Sampaio et al, 2006;Sporis, Sango, Vucetic, & Masina, 2006). Centres' anthropometric and technical characteristics appear to have an important influence in these defensive tasks.…”
Section: Discussionmentioning
confidence: 99%
“…and is used to identify the existence of specific morphological types in each sport modality and playing position. The importance of this parameter has been demonstrated in studies investigating the ideal physical profile in different modalities 3,[6][7][8][9][10] . Some studies have used somatotype analysis to establish the ideal physical profile of volleyball players in each playing position in order to facilitate training programs 3,6,11,12 .…”
Section: Introductionmentioning
confidence: 99%